Textlinguistische Gemeinsamkeiten und Unterschiede in einer deutsch-englischen Selbstübersetzung - Salvato, Lucia (ANNALI. SEZIONE GERMANICA. Rivista del Dipartimento di Studi Letterari, Linguistici e Comparati dell’Università degli studi di Napoli L’Orientale, 2021)
The object of this study is a contrastive analysis of the German (1992) and the self-translated English version (2001) of Ruth Klüger’s autobiography. Unlike the traditional method of contrastive linguistics, this study is a linguistic reflection on a written work and its self-translation. These are analyzed through text-linguistic questions by means of a grammatical-linguistic study, to identify analogies and divergences in the German and English language usage by the writer, and to highlight possible linguistic deviations from the standard structure. Especially the syntactic analysis aims at verifying whether and how, despite different realizations of the topic-comment structure, the information packaging is preserved in the translation. The analysis demonstrates that deviations from the unmarked sequence SVO in favor of the focus at the beginning of the sentence are mainly in German, while in English Klüger maintains the linear syntactic word order.